Debate - The Trafficking Protocol and the Anti-Trafficking Framework: Insufficient to address exploitation - Baer, Kathryn (Anti-Trafficking Review, 2015)
The Trafficking Protocol[1] has shaped and advanced a global movement against human trafficking; notably through establishing a global definition and creating criminal justice remedies befitting an international crime.[2] Borne out of and including the Protocol, a global anti-trafficking framework has emerged. This framework reflects these two central tenets at international, regional and national levels and includes initiatives by States not party to the Protocol, such as Singapore. However, the emphasis on these tenets, which comprise only part of a robust anti-trafficking strategy, has rendered the existing framework insufficient to address exploitation. [1] In full: Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children [2] K H Heinrich, ‘Ten Years After the Palermo Protocol: Where are Protections for Human Trafficking?’, Human Rights Brief 18, no.1, 2010, retrieved 5 January 2015, http://digitalcommons.wcl.american.edu/cgi/viewcontent.cgi?article=1145&context=hrbrief ; K E Hyland, The Impact of the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, Human Rights Brief 8, no. 2, 2001, retrieved 5 January 2015, http://digitalcommons.wcl.american.edu/cgi/viewcontent.cgi?article=1492&context=hrbrief